Effects of full-body exercise-based pulmonary rehabilitation in patients with idiopathic pulmonary fibrosis: a systematic review and meta-analysis protocol - Yu Chen; Yi Pan; Han Yang; Luo Quan; Shurong Wang; Youli Xu (BMJ Open)
Introduction Idiopathic pulmonary fibrosis (IPF) is a chronic lung disease characterised by progressive and irreversible fibrosis of the lung parenchyma, resulting in reduced lung function. Since conventional medicines can be associated with low effective rates and adverse events, pulmonary rehabilitation may be a promising non-pharmacological therapy for IPF. Thus, we aimed to evaluate the effects of full-body exercise-based pulmonary rehabilitation on patients with IPF by conducting a systematic review and meta-analysis of randomised controlled trials (RCTs).Methods and analysis This systematic review and meta-analysis has been registered in the International Prospective Register of Systematic Reviews (PROSPERO). From inception to 31 August 2022, electronic databases in English and Chinese were searched, including PubMed, Embase, Web of Science, Cochrane Central Register of Controlled Trials among the English databases. China National Knowledge Infrastructure, Chinese Biomedical Literature, VIP Chinese Science and Technology Periodical, and Wan Fang Data were among the Chinese databases. Two independent reviewers then screened the potential RCT studies, which were analysed according to the Cochrane Handbook criteria. The efficacy and safety of full-body exercise pulmonary rehabilitation for IPF were evaluated based on outcomes, including exercise capacity measured by 6 min walking distance and quality of life measured by St. George’s Respiratory Questionnaire. Lung function was measured based on the forced vital capacity, total lung capacity, diffusing capacity of the lungs for carbon monoxide and dyspnoea assessed by the modified Medical Research Council scale.Ethics and dissemination Ethical approval was not required for this systematic review and meta-analysis. Results will be published in a peer-reviewed journal and presented at conferences.PROSPERO registration number CRD42021284293.